Trends and transitions: mapping a decade of conservation research in Brazil’s federal protected areas - Ana Carolina da Silva; Franklin Galvão; Nelson Cosmo (Terr@ Plural)
Investment in research in protected areas provides subsidies for improving the management and conservation of these environments, such as creating new conservation units and promoting sustainable tourism. This paper aimed to analyse the evolution of published studies on federally protected areas in Brazil through a systematic review of 2,282 papers in the Scopus database from 2011 to 2022. There was a growing increase in the number of articles till an abrupt decrease in 2022. The VosViewer software identified niches of the most used keywords linked to conservation, Atlantic Forest, and protected areas. The study highlights the challenges faced when performing research activities in federal protected areas in Brazil, such as access to remote areas and climate instability. The COVID-19 pandemic impacted research, together with the dismantling of scientific institutions by the Brazilian government compromised scientific progress, reflected in a decline of 54% in publications. International collaboration was emphasized, highlighting the importance of disseminating scientific knowledge for environmental preservation and carefully selecting keywords to promote the accessibility and visibility of articles.